2021
DOI: 10.1039/d1fo00979f
|View full text |Cite
|
Sign up to set email alerts
|

MUFA in metabolic syndrome and associated risk factors: is MUFA the opposite side of the PUFA coin?

Abstract: Omega-9 fatty acids represent one of the main mono-unsaturated fatty acids (MUFA) found in plant and animal sources. It can be synthesized endogenously in the human body, though not fully...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 92 publications
1
11
0
Order By: Relevance
“…Omega-9 FA are synthesized endogenously in the human body but does not provide body’s full requirements; hence they are considered partially essential fatty acids. Studies indicate the beneficial effects of MUFA’s for CVD to be consistent with PUFAs, namely, for the relief systolic blood pressure (SBP) and diastolic blood pressure (DBP), improvement of high LDLc, and triglycerides (TAG) levels [ 122 ]. Furthermore, inclusion of OA (omega-9) in a diet—together with other nutrients known to be cardioprotective such as eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), folic acid, and vitamins A, B-6, D, and E—enhanced clinical values while reducing a variety of risk factors in men with peripheric vascular disease and intermittent claudication (PVD-IC), announcing itself as new evidence of the potential nutraceutical role for these compounds in the reduction of PVD-IC symptoms [ 123 ].…”
Section: Discussionmentioning
confidence: 99%
“…Omega-9 FA are synthesized endogenously in the human body but does not provide body’s full requirements; hence they are considered partially essential fatty acids. Studies indicate the beneficial effects of MUFA’s for CVD to be consistent with PUFAs, namely, for the relief systolic blood pressure (SBP) and diastolic blood pressure (DBP), improvement of high LDLc, and triglycerides (TAG) levels [ 122 ]. Furthermore, inclusion of OA (omega-9) in a diet—together with other nutrients known to be cardioprotective such as eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), folic acid, and vitamins A, B-6, D, and E—enhanced clinical values while reducing a variety of risk factors in men with peripheric vascular disease and intermittent claudication (PVD-IC), announcing itself as new evidence of the potential nutraceutical role for these compounds in the reduction of PVD-IC symptoms [ 123 ].…”
Section: Discussionmentioning
confidence: 99%
“…Monounsaturated fat (MUFA) found in plant and animal sources, present several health benefits, including the prevention of metabolic syndrome and its complications (Sheashea M et al, 2021). As our study shows that MUFA (%) from in nature foods was lower in group with the highest BMI, it is strongly suggested that dietary intervention adding MUFA can lead to anti-inflammatory effects and can decrease chronic inflammation ameliorating the general metabolic profile (Ravaut G et al, 2020).…”
Section: Discussionmentioning
confidence: 67%
“…Also, sweet grass increases the concentration of MUFA in milk because fresh grass increases milk fatty acids that are ruminal biohydrogenation intermediates (C18:1, C18:2, C18:3). It has been demonstrated that MUFA can improve glycemic control and prevent the development of metabolic syndrome and its complications (Sheashea et al ., 2021). Similar results are shown in the intervention with Acacia farmesiana , dried grape pomace, and MMG that increased the long-chain fatty acids, like linoleic and alpha-linolenic acids.…”
Section: Discussionmentioning
confidence: 99%